“Optimización del proceso de producción de alimento para cerdos mediante el diseño y construcción de una máquina semiautomática en la empresa la Granja Herrera” - Montenegro Mera, Franklin Benigno (2021)
There is a main problem at the farm breeding pigs from Herreras’ family, it is because the exceded time to prepare the pigs food that carries big costs such as power consumption, unnecesary displacement and the others things, in which it produces high cost for the owners. In order to find a solution, there are three ways that they were analized with the follow parmeters values like the ergonomic machine, the function machine, speed process product. Even if the Alternative B were the solution with a final quality production. According to the investigation for this machine and its performance in preparing the food and feeding the pigs by C. Riba (2002), the structure is based in four stages for developing. However, in the definition specify the Budget proposal scale that require each pig for feeding in every stage of growing. Moreover, In the next stage, the conceptual design analized the alternative of solution to get the basic architectural machine for processing food for the pigs. In addition, at the design stage of materialization indicates three elements such as materials, shapes, proportions and manufacturing. And finally, the last design stage are detailed the plan of technical part and the overview plan denoted technical specifications from the processing machine.